"Put It Out There That You Are Willing To Talk About Anything": The Role of School Counselors in Providing Support to gay and Bisexual Youth. Issue 1 (October 2013) - Roe, Stuart
This study examines how gay and bisexual adolescents identify and access support from their school counselor using a phenomenological inquiry approach. Gay and bisexual adolescents were interviewed regarding their experiences with their school counselors and reported that they believed school counselors should be supportive by virtue of their title. Participants used various methods to determine if their school counselor was supportive including ascertaining political beliefs, relying on the past history of the school counselor-student relationship, observing supportive symbols in school counseling offices, and relying on knowledge gained from other students. Students reported that school counselors are most helpful when they simply listen to students' concerns and state directly that they are willing to discuss LGBT issues. Barriers to accessing support from school counselors included student concerns regarding confidentiality and fears of being judged or treated differently by their school counselor. The article also discusses study strengths and limitations.